ANALISIS FASIES DAN LINGKUNGAN PENGENDAPAN FORMASI TUBAN, JAWA TIMUR UTARA - Salatun Said; Windiastuti Windiastuti (Jurnal Ilmiah MTG, 2009)
The purpose of this study are understanding of the facies type, distribution and its environment. On the basis of the sedimentological characteristic, Tuban Formation can be devided into 5 major facies namely mudstone, wackstone, packstone, grainstone and bindstone.These facies will be described into detail so the each facies that different in characterictic such as texture and composition will have the different name. Environment interpretation from these facies reveals a restricted to open marine-shallow condition. According to reef facies sub-division this environment could be divided into lagoon, back reef, core reef, and fore reef. The presence and distribution of those facies were characterized the fringing reef.